Glutamate and modeling of schizophrenia symptoms: Review of our Findings: 1990-2014 - Gargiulo, Pascual Angel (2014)
In the early 90s, we studied the role of perception disturbances in schizophrenia in our first clinical approaches, using the Bender test in schizophrenic patients. Results were clear, showing a shape discrimination failure. Following this initial results, we reproduced nuclear symptoms of schizophrenia in animal models, showing that perceptual disturbances, acquisition disturbances, decrease in affective levels and working memory disturbances can be induced by specific N-methyl-D-aspartic acid (NMDA) glutamatergic blockade within the nucleus accumbens septi (NAS). We studied also another glutamatergic and dopaminergic drugs, finding that a decrease in glutamatergic transmission within NAS led to cognitive disturbances and affective flattening. An increase in glutamatergic transmission fully enhances cognition in the tasks used. Dopaminergic D-2 antagonists partially improved cognition. Our results link the proposed corticostriatal dysfunction with the thalamocortical disturbances underlying perceptual problems, but also influencing affective levels and cognitive variables. According to our translational findings, core schizophrenia symptoms may be translationally reproduced antagonizing NMDA receptors within NAS, and improved blocking the glutamate auto-receptor. Dopaminergic transmission appears to have a role in therapeutic but not in the early pathophysiology of schizophrenia.